Successful Therapeutic Management of Two Critical Cases of Canine Monocytic Ehrlichiosis - Jena, B. R.; Samal, P.; Panda, S. K.; Patra , R. C. (International Journal of Livestock Research, 2020)
Canine Monocytic Ehrlichiosis(CME) is a fatal tick borne disease caused by Ehrlichia canis, transmitted by the tick, Rhipicephalus sanguineus. Epistaxis, petechial hemorrhage, hematuria, fever, thrombocytopenia and anemia are some important clinico-pathological findings of this disease. Two dogs (one Labrador and another German Shepherd) were presented to TVCC with above mentioned clinical symptoms. Examination of blood parameters revealed anemia and thrombocytopenia. Morulae bodies were found within the monocytes in blood impression smear of labrador dog. Both the dogs were positive for E. canis by a SNAP 4Dx Plus Test Kit, which confirmed the case as CME. Whole blood transfusion was carried out in Labrador dog. Both the animals were treated with doxycycline@5mg/kg, b.i.d. along with other supportive medications. After a month of treatment, the animals showed an uneventful recovery. Thus, doxycycline therapy, whole blood transfusion along with other supportive were found useful in the management of critical cases of CME.